Changes in Uterine Cancer Incidence Rates in Egypt. (14th June 2018) - Alshahrani, Saad; Soliman, Amr S.; Hablas, Ahmed; Ramadan, Mohamed; Meza, Jane L.; Remmenga, Steven; Seifeldein, Ibrahim A.; Chamberlain, Robert M.
Abstract : Background . Uterine cancer is one of the top-ranking cancers in women with wide international variations in incidence rates. Developed countries have higher incidence rates than the developing countries. Egypt has significantly lower incidence of uterine cancer than other countries in the Middle East. This study aimed at verifying the incidence rate of uterine cancer and characterizing the demographic and clinical profiles of patients residing in the Gharbiah province in the Nile delta region of Egypt. Methods . Data from 660 uterine cancer patients diagnosed during the period of 1999 to 2010 were abstracted from the Gharbiah Cancer Registry, the only population-based registry in Egypt. The data included age, marital status, number of children, residence, smoking, occupation, date and basis of diagnosis, tumor topography, morphology, stage and grade, and treatment. Crude rate, age-standardized rate (ASR), and age-specific rate were calculated and associated with demographic and clinical characteristics of patients. Results . The study confirmed the low ASR of uterine cancer in Egypt, (4.1 per 100, 000 (95% CI: 3.8–4.4)). The incidence rate increased significantly over the 12-year period. The crude rate (CR) was 1.95, 95% CI (1.64–2.25) in 1999–2002; 2.9, 95% CI (2.5–3.2) in 2003–2006; and 3.5, 95% CI (3.1–3.9) in 2007–2010. The rate ratio was 1.5, 95% CI (1.2–1.8) in 2003–2006 and 1.8, 95% CI (1.5–2.2) in 2007–2010 compared to 1999–2002. The majority of patients (83%) were postmenopausal with the highest age-specific rate in the 60–69-year age group (22.07 per 100, 000 (95% CI: 19.3–25.2). The majority of patients were diagnosed at early stages (60% localized and 5% regional), had adenocarcinoma (68%), and resided in urban areas (54%). Conclusions . The study confirmed the low incidence rate of uterine cancer in the Gharbiah province of Egypt and significant increase in incidence in recent years. Future studies should focus on verifying the possible effect of hysterectomy on lowering the incidence, the factors related to the changes in rates between rural and urban areas, and the possible impact of nutritional and epidemiologic transitions on the increasing rates.